Socioeconomic participation of persons with hemophilia: Results from the sixth hemophilia in the Netherlands study - Erna C. van Balen; Shermarke Hassan; Cees Smit; Mariette H. E. Driessens; Erik A. M. Beckers; Michiel Coppens; Jeroen C. Eikenboom; Hélène L. Hooimeijer; Frank W. G. Leebeek; Evelien P. Mauser‐Bunschoten; Lize F. D. van Vulpen; Saskia E. M. Schols; et al. (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background and objectives Treatment availability and comprehensive care have resulted in improved clinical outcomes for persons with hemophilia. Recent data on socioeconomic participation in the Netherlands are lacking. This study assessed participation in education, in the labor market, and social participation for persons with hemophilia compared with the general male population. Methods Dutch adults and children (5–75 years) of all hemophilia severities (n = 1009) participated in a questionnaire study that included sociodemographic, occupational, and educational variables. Clinical characteristics were extracted from electronic medical records. General population data were extracted from Statistics Netherlands. Social participation was assessed with the PROMIS Ability to Participate in Social Roles and Activities short form, with a minimal important difference set at 1.0. Results Data from 906 adults and children were analyzed. Participation in education of 20 to 24 year olds was 68% (general male population: 53%). Educational attainment was higher compared with Dutch males, especially for severe hemophilia. Absenteeism from school was more common than in the general population. The employment‐to‐population ratio and occupational disability were worse for severe hemophilia than in the general population (64.3% vs. 73.2% and 14.7% vs. 4.8%, respectively), but similar for nonsevere hemophilia. Unemployment was 5.4% (general male population: 3.4%). Absenteeism from work was less common (38% vs. 45.2%). Mean PROMIS score was similar to or higher than in the general population (54.2; SD 8.9 vs. 50; SD 10). Conclusion Socioeconomic participation of persons with nonsevere hemophilia was similar to the general male population. Some participation outcomes for persons with severe hemophilia were reduced.